El clima laboral y sus incidencias en el desempeño de los trabajadores del área de talento humano de la constructora diploter s.a. diseño ingeniería y proyectos de Guayaquil en el periodo 2016- 2017 - Maigua Moreno, Jeniffer Josefina (2016)
The construction Diploter S.A. Design Engineering and Projects Guayaquil is a company legally incorporated in the city of Guayaquil; its main activity is to provide good service and quality of work at national level. Due to the great demand on their activities every day is done, we have created several activities for better comfortable work environment, achieving better performance on workers in order to demonstrate the quality and commitment of the company at the time of the work done. In this research the causes and positive-negative consequences of a working environment that may occur in the area of human talent is analyzed Constructor Diploter S.A. To measure the dissatisfaction that exists in the company, we use a survey form to collect the necessary information….